Helicobacter pylori en heces, detección con portadores asintomáticos de 30 a 40 años comunidad San Gregorio cantón Babahoyo los ríos primer semestre 2015 - Castro Saavedra, William Fernando (2015)
Anemia can be due to different causes and these . H pylori infection is a threat as in populations where few controls hygienic sanitation lifestyles among others, leads to develop persistent infections in many situations by years of asymptomatic chronically, causing complications in many cases can be fatal, including coronary alteration or the development of invasive metastatic adenocarcinoma. In previously untreated patients, serologic tests offer a reasonable alternative to bring the diagnosis of H pylori infection, but should be aware that these tests have values of S and E insufficient to be used as the only diagnostic method, reserving as most useful techniques for epidemiological study of infection. The results for the CerTest h. Pylori test card positioned this diagnostic method as an excellent clinical and epidemiological tool to study populations exposed to suspected asymptomatic infection with H pylori.Creemos that still need further study and that a greater number of people to be included, to register this new diagnostic method as a possibility to establish the presence or absence of H pylori infection in the general population without the need for endoscopy and reach the diagnosis of asymptomatic populations and prevent future complications in them.